Artisan‐style iris‐claw intraocular lens implantation in patients with uveitis. Issue 11 (November 2019) - Negretti, Guy S.; Chan, Weng Onn; Pavesio, Carlos; Muqit, Mahiul M.K.
Abstract : Purpose : To study the use of iris‐claw Artisan intraocular lenses (IOLs) in patients with uveitis. Setting : Moorfields Eye Hospital, London, England. Design : Retrospective case series. Methods : Data on all patients with anterior uveitis, intermediate uveitis, and panuveitis who had anterior‐fixated Artisan IOL insertion between January 2014 and July 2019 at Moorfields Eye Hospital were assessed. Patients who had less than 2 months of follow‐up were excluded from the analysis. Results : The study comprised 11 patients. The mean age of the 7 women and 4 men was 61 years ± 14 (SD). The mean follow‐up was 1.7 years. After Artisan IOL insertion, the corrected distance visual acuity (CDVA) improved significantly from 20/200 to 20/50 ( P = .02). No patients had a significant flare‐up of their uveitis after the surgery, and there were no intraocular pressure‐related events. One patient developed cystoid macular edema, which responded to treatment. Conclusion : This case series showed the efficacy and safety of Artisan‐style IOLs in patients with a history of uveitis. After the Artisan IOL insertions, these patients experienced a significant improvement in CDVA with minimal side effects.